SURVEY OF LONG-TERM VENTILATION IN HOSPITALS OF THE JAPANESE NATIONAL HOSPITAL ORGANIZATION - IMAI, Takashi; FUKUNAGA, Hidetoshi; NISHIMA, Sankei; SHINNO, Susumu; ISHIKAWA, Yuka; TATARA, Katsunori (Japanese Journal of National Medical Services, 2005)
We conducted a survey of current conditions for patients receiving long-term ventilator-assistance in hospitals belonging to Japanese National Hospital Organization. The subjects were 2055 patients managed by 80 hospitals. Among these patients, 1, 114 had muscular dystrophy, 410 had ALS, 236 had other neuromuscular disorders, 205 had severe motor and intelligence disorder (SMID) and 30 had other conditions. There were 53 kinds of ventilators in the 80 hospitals and the average number of ventilators per hospital was 4.9. With regard to ventilator portability, 51% were portable, whereas, 148 (7.2%) were critical care ventilators. The period of mechanical ventilation was more than 10 years in 148 cases and more than 20 years in 11. Among the 2, 055 patients, 1, 215 were tracheotomized and 801 were receiving noninvasive positive pressure ventilation. The experience of go out was 54.9% for muscular dystrophy, 23.2% for ALS and 20.8% for SMID. The practice rate of physiologic response monitoring was low. For example, pulse oximetry was done in 35.4% of patients with muscular dystrophy, and 40.7% of those with ALS, compared with 92.8% of patients with SMID. We think that these conditions in which many models are mixed and monitoring is inadequate increase the risk of ventilator-associated accidents. It is concluded that the number of patients requiring long-term ventilation in the Japanese National Hospital Organization is increasing and that it will become important to collect exact information to implement measures to counteract any associated problems related.